STRATEGI REBRANDING MELALUI MARKETING PUBLIC RELATION PADA RADIO MUSIK GEN 98,7 FM - Valianty Sariswara (Universitas Pakuan, 2022)
This research elaborates the rebranding strategy of Gen 98.7 fm through MPR in relation to the decline of Gen listeners in 2016. If no action was taken, it is feared that their decline of listeners will affect the brand. Wanting to strengthen the Gen FM as a radio station that supports local music and provides content that is pooled locally. This research illustrates how the rebranding process of Gen fm suara musik terkini into gen fm generasi suara musik Indonesia, accomplished in perspective to Marketing Public Relation. To achieve that goal, GEN FM used strategy rebranding through Marketing Public Relation as tools. The research approach used was a qualitative approach to acquire descriptive written and oral data thus resulting in a deep explanation about rebranding through Marketing Public Relation. The research results show that the rebranding strategy of Gen 98.7 fm GSMI was a success at a programming level and resulted in a high engagement in terms of target market.